Black politics in New Deal Atlanta - Ferguson, Karen (Karen Jane) (John Hope Franklin series in African American history and culture., 2002)
In 1932, Atlanta had the South's largest population of educated African Americans. However, Jim Crow's dictates meant they were almost entirely excluded from public life. Ferguson shows how Roosevelt's New Deal opened up oppportunities for black Atlantans struggling to acheive full citizenship.